Niklas Luhmann and Cybernetics - Paetau, Michael (Journal of Sociocybernetics, 2014)
Even though Niklas Luhmann himself never declared his own approach as a cybernetic one, and even if the relationship between systems theory and cybernetics is still not clearly defined in every way, it seems to be legitimate to classify Luhmann’s Theory of Social Systems into the field of cybernetics approaches, more precisely as a socio-cybernetic one. Beside the concept of autopoiesis by Maturana and Varela there are various systems thinkers and cyberneticists like Wiener, Ashby, Shannon, Bateson, von Foerster who influenced Luhmanns work deeply. Certainly he fits the cybernetic principles into his theory rather idiosyncratically and partly after some significant revisions, but one can argue that Luhmann’s Theorie of Social Systems is the conclusion of a confrontation of the mayor issues of cybernetic discourse with the European philosophical tradition. In the following article it is discussed the question in what extent we can include Luhmann’s work into the cybernetic tradition. Which are the significant connection-points between cybernetics and Luhmann’s work? What is the relevance of this connection for Luhmanns own theoretical development? Which are the congruences and which are the differences? To what extent is Luhmann’s Theory of Social Systems even though his critical distance - integrable into the spectrum of the approaches of ``New Cybernetic’’ (as Geyer & van der Zouwen formulated in 1986)? After a short discussion on what is characterizing a theory as a cybernetic one, the article reconstructs Luhmann’s critical debate on the most important theoretical problems of cybernetics and finally it will sketch out Luhmanns answer to this debate, which he gives in his own concepts. For Luhmann the fascination of cybernetics consists in explaining the problem of constancy and invariance of systems in a highly complex and dynamical world by observing communication processes. This makes cybernetics to a definitive non-ontological approach and brings it near to the functionalistic sociology.